Economic Narratives and the Legitimacy of Foreign Direct Investments - Linsi, Lukas (2022)
In the 1990s, the primary focus of the international investment regime shifted from the restriction and regulation towards the promotion and attraction of foreign companies. Dominant accounts in the international political economy literature emphasize the role of interests and institutions in explaining this policy shift but pay little attention to their legitimation. This article argues that transformations in dominant economic discourses—and in particular the rise of the competitiveness narrative—played an important role in granting legitimacy to this U-turn in international economic affairs. To test the argument, the article focuses on the impact of the differential changes in the portrayal of greenfield and mergers and acquisitions (M&A) inward foreign direct investments (IFDI) in economic discourses in the UK before and after the rise of the competitiveness narrative. In line with the theoretical argument, findings indicate that individuals who passed their early adulthood in a period in which the narrative of economic statism was still prevalent hold notably more skeptical views of M&A IFDI even though they are otherwise not more opposed to investments from abroad. A causal mediation analysis lends further empirical support to the argument.